2002
DOI: 10.1051/0004-6361:20020895
|View full text |Cite
|
Sign up to set email alerts
|

Warps and correlations with intrinsic parameters of galaxies in the visible and radio

Abstract: Abstract. From a comparison of the different parameters of warped galaxies in the radio, and especially in the visible, we find that: a) No large galaxy (large mass or radius) has been found to have high amplitude in the warp, and there is no correlation of size/mass with the degree of asymmetry of the warp. b) The disc density and the ratio of dark to luminous mass show an opposing trend: smaller values give more asymmetric warps in the inner radii (optical warps) but show no correlation with the amplitude of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…We present the whole sample of 250 spirals and 26 lenticulars, with limits logr25 > 0.60, B t < 14.5, δ < 0 • , −2.5 < t < 7. It is especially suitable for statistical analysis and, indeed, has already been used to study the relation between intrinsic parameters and warps by Castro-Rodríguez et al (2002). The catalog may obviously be used to choose which galaxies are to be observed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…We present the whole sample of 250 spirals and 26 lenticulars, with limits logr25 > 0.60, B t < 14.5, δ < 0 • , −2.5 < t < 7. It is especially suitable for statistical analysis and, indeed, has already been used to study the relation between intrinsic parameters and warps by Castro-Rodríguez et al (2002). The catalog may obviously be used to choose which galaxies are to be observed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the Zinn et al (2003) study who possibly identified CMa stars in the so-called southern arc of the CMa ring. Accreting Galactic satellites could be responsible for the creation of the observed Milky Way warp (Castro-Rodríguez et al 2002). Evidence for the existence of a Galactic warp for the inter-stellar gas and dust are long dated since early HI observations (Oort et al 1958), and more recent inter-stellar diffuse dust emission (Freudenreich et al 1994;Freudenreich 1996) studies.…”
Section: Introductionmentioning
confidence: 99%
“…The warp angle β seems to better represent the curvature of the warped disk (Ann & Park 2006). There are different definitions of warp asymmetry in the literature (Reshetnikov & Combes 1998;Garcia-Ruzi et al 2002;Castro-Rodriguez et al 2002) but we used the following definition of…”
Section: Results (A) Morphologymentioning
confidence: 99%